Development of Professional 3D Pageflip Based E-Book Media on Elasticity and Hooke’s Law Material - Nisa, Badratun; -, Juniar Afrida; Idris, Jamaluddin (Al-Khazini: Jurnal Pendidikan Fisika, 2024)
Based on observations made by researchers at SMAN 1 Indrapuri, the media used is textbooks and sometimes educators also display videos as additional media. From these problems the researcher is interested in carrying out research at the SMA / MA level. This study aims to determine the feasibility level of media e-book with 3D PageFlip Professional on Elasticity and Hooke’s Law. This research uses Research and Development (R&D) research with the ADDIE model. The ADDIE model has several stages, namely analysis, design, development, implementation and evaluation. The instruments used in this study were validation sheets from media experts and material experts. The results obtained from the validation of media experts were 94.8% and material experts were 97.4% with very decent criteria. It can be concluded that learning media with 3D PageFlip Professional can be used in the learning process.